2023
DOI: 10.1186/s12889-023-15155-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender and urban-rural influences on antibiotic purchasing and prescription use in retail drug shops: a one health study

Abstract: Introduction Few studies have reported antibiotic purchases from retail drug shops in relation to gender in low and middle-income countries (LMICs). Using a One Health approach, we aimed to examine gender dimensions of antibiotic purchases for humans and animals and use of prescriptions in retail drug shops in Bangladesh. Methods We conducted customer observations in 20 drug shops in one rural and one urban area. Customer gender, antibiotic purchas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This concords with the study that showed that sex differences are contextual and correlate with other sociodemographic factors especially education level and socioeconomic levels, with females having relatively more knowledge than their counterparts [ 35 ]. This also coincides with the study from Bangladesh that revealed that men leaned more towards buying unprescribed animal drugs compared to women; similarly, women-owned farms were also more likely to use fewer antimicrobials in farms compared to men-owned ones [ 36 38 ]. This discrepancy could be attributed to factors such as: i) women have more access to information; a cross-sectional study in Thailand showed that women had 1.8 times more odds of accessing information on AMR than men [ 39 ], ii) women have more knowledge on antibiotics because they tend to use prescribed medicines and are more aware of efficacy of medicine compared to men [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…This concords with the study that showed that sex differences are contextual and correlate with other sociodemographic factors especially education level and socioeconomic levels, with females having relatively more knowledge than their counterparts [ 35 ]. This also coincides with the study from Bangladesh that revealed that men leaned more towards buying unprescribed animal drugs compared to women; similarly, women-owned farms were also more likely to use fewer antimicrobials in farms compared to men-owned ones [ 36 38 ]. This discrepancy could be attributed to factors such as: i) women have more access to information; a cross-sectional study in Thailand showed that women had 1.8 times more odds of accessing information on AMR than men [ 39 ], ii) women have more knowledge on antibiotics because they tend to use prescribed medicines and are more aware of efficacy of medicine compared to men [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, as shown in Uganda’s low-income regions, men tend to have higher rates of self-medication, due to greater purchasing power that enables them to obtain medication from the private sector, a more expensive option unavailable to women ( Ocan et al , 2014 ). Other studies have also shown that men are more likely to buy antibiotics without a prescription, compared with women ( Jones et al , 2022 ; Rousham et al. , 2023 ).…”
Section: Resultsmentioning
confidence: 95%
“…In the LMICs’ pharmaceutical sector, approximately two-thirds of antibiotics are used for self-medication ( WHO, 2015 ). Self-medication is prevalent in some sub-Saharan countries such as Tanzania, Cameroon and Namibia, ranging from 50% to 60% in some regions ( Simon and Kazaura, 2020 ), as well as in other LMICs such as India, with around three-quarters of antibiotics bought without prescriptions in some areas ( Rousham et al. , 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is important in Bangladesh, given extensive colistin-resistant Escherichia coli in broiler meat and chicken feces [44][45][46], exacerbating resistance among patients to colistin in Bangladesh [47][48][49][50]. Over-the-counter dispensing of antibiotics is also common in Bangladesh and a concern, especially when this involves 'Watch' and 'Reserve' antibiotics [51][52][53][54] Overall, activities to enhance the appropriate use of colistin in both animals and humans are essential as colistin still remains the antibiotic of choice for multiple drug-resistant gram-negative bacterial infections (MDR-GNB). This includes carbapenem-resistant Acinetobacter baumannii (CRAB) as well as other pathogens resistant to the new antimicrobial agents [55][56][57].…”
Section: Introductionmentioning
confidence: 99%